BPI (BELARUSSIAN POLYTECHNICAL INSTITUTE): ON THE WAY TO RE-ORGANIZATION AND FORMATION (1920–1930) - K. I. Balandin; A. N. Kouksa (Наука и техника)
Formation of engineering higher education institution and restoration processes of higher agricultural school and inMinskare closely interrelated with each other. TheBelarussianNationalTechnicalUniversityand theBelarussianStateAgriculturalAcademyare celebrating their jubilees in 2010.